The Effect of Self-Control, Self-Concept, and Lifestyle on Consumtive Behavior in Online Shopping on Students of Batam University - Fathonah, Siti; Ngaliman, Ngaliman; Luthfi, Andi M. (Universitas Batam, 2023)
The reason for this study was to examine the impact of Self-Control, Self-Concept, and Lifestyle on Consumptive Behavior in Online Shopping on Students of Batam University. The method applied in this study is the quantitative method . The populace utilized in this study were students of Batam University with a total of 2,814 students at 2022, while the sampling was 97 respondents. Data collection primarily involved administering questionnaires to the participants. Data processing in this study used the SPSS Software version 25 program. Results from the partial t-test revealed that self control and lifestyle significantly influenced consumptive behavior in online shopping, whereas self concept did not demonstrate a significant effect. However, when these factors were considered together, they collectively showed a considerable impact on consumtive behavior in online shopping. The worth of R Square on self control, self concept, and lifestyle factors influrncing consumtive behavior in online shopping is 20.9% and the remaining 79.1% are explained by others relevant variables.